Genealogy of the Prussian Line of the Quandt Family Written by Johann Jacob Quandt, the Last Bearer of the Surname - Citavičiūtė, Liucija (Senoji Lietuvos literatūra, 2024)
Johann Jacob Quandt (1686–1772), the general superintendent of Prussia, is well-known in the history of Lithuanian literature and culture as a promoter of Lithuanian writing in eighteenth-century Prussian Lithuania. About a dozen Lithuanian books were produced under his care. He involved students and graduates of the University of Königsberg in the writing process. It is not known what prompted Quandt to write the genealogy of his family and when he started this work, but it is known that he finished it in 1756 and left the manuscript to his nephew, Johann Christoph Bohlius (1703–1785). After his death, Quandt’s personal archive was reviewed and some of the documents were included in the obituary ‘To the Man While He Lived […] Magnificent [...] Johann Jacob Quandt’ (Viro, dum viveret, magnifico [...] Johanni Jacobo Quandt [...], Königsberg, 1772). This obituary was the first publication of the genealogy of eight generations of the Quandt family. The Quandts established themselves in Königsberg in the sixteenth century; the Teutonic Knights or their descendants may have been the founders of this branch of the family. The obituary with the genealogy of the Quandts is kept at the National Library of Poland in Warsaw (Biblioteka Narodowa w Warszawie, sign. SD XVIII.4.1170 adl.). Quandt’s manuscript has not survived or has not been found. Many of the men of the Quandt family had been educated at the University of Königsberg, served in government posts, were priests, and one was a merchant engaged in commerce. The men of the family usually chose the daughters of priests as their wives, making it an elite family. Of the Quandt family, three of its representatives are better known today: Jacobus, the great-grandfather of Johann Jacob Quandt, his father Johann, and our Johann Jacob Quandt, the general superintendent of Prussia, the preacher of the royal court, and first professor of theology. The appended source was translated from the Latin by Dr Mindaugas Strockis.